PEMAKNAAN FATHERLESS SEBAGAI KETIDAKHADIRAN EMOSIONAL AYAH DALAM FILM ANDAI AYAH IBU TIDAK MENIKAH DENGAN AYAH - Nazwa Mutiara Ramadhani; Ririn Puspita Tutiasri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Fatherlessness is commonly understood as the physical absence of a father. However, contemporary media increasingly portrays fatherlessness as the absence of a father's emotional involvement in a child's life. This study aims to analyze how Generation Z interprets fatherlessness as emotional absence in the film Andai Ibu Tidak Menikah dengan Ayah. This research employed a qualitative approach using Stuart Hall's Reception Analysis theory. Data were collected through in-depth interviews with Generation Z informants aged 20–25 years who had watched the film. The findings reveal that most informants interpret fatherlessness not merely as the physical absence of a father but as the failure of a father to establish emotional closeness, communication, attention, and active involvement in the child's life despite being physically present. The film also influenced several informants to reconstruct their understanding of fatherlessness from physical absence to emotional absence. Furthermore, the reception analysis identified dominant-hegemonic, negotiated, and oppositional positions, indicating that audience interpretations were shaped by personal experiences, family backgrounds, and emotional relationships with their fathers. This study contributes to communication studies by demonstrating that film representations play an important role in constructing Generation Z's understanding of fatherlessness as an issue of emotional presence rather than solely physical absence.